Intracranial interhemispheric osteochondrolipoma: Diagnostic and surgical challenges in an extremely rare entity. Issue 5 (16th May 2016) - Rajeshwari, Madhu; Suri, Vaishali; Kaur, Kavneet; Suri, Ashish; Garg, Ajay; Sharma, Mehar Chand; Sarkar, Chitra
Abstract : Intracranial lipomas are rare developmental lesions, predominantly occurring in the interhemispheric location. Osteochondrolipoma is an extremely rare variant of lipoma with osseous and chondroid differentiation. We present a case of interhemispheric osteochondrolipoma, in a 2.5‐years‐old male child which was detected antenatally, in association with corpus callosum agenesis. The lesion progressively increased in size with resulting compression of surrounding structures, and was subjected to microsurgical decompression. To the best of our knowledge, this is the first case of intracranial interhemispheric osteochondrolipoma in the existing medical literature. Peculiarities of this case and the diagnostic and surgical challenges are discussed.